2021
DOI: 10.1098/rsob.210004
|View full text |Cite
|
Sign up to set email alerts
|

From infection to cancer: how DNA tumour viruses alter host cell central carbon and lipid metabolism

Abstract: Infections cause 13% of all cancers globally, and DNA tumour viruses account for almost 60% of these cancers. All viruses are obligate intracellular parasites and hijack host cell functions to replicate and complete their life cycles to produce progeny virions. While many aspects of viral manipulation of host cells have been studied, how DNA tumour viruses manipulate host cell metabolism and whether metabolic alterations in the virus life cycle contribute to carcinogenesis are not well understood. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 90 publications
(120 reference statements)
1
14
0
Order By: Relevance
“…Previous studies have found that viral carcinogenesis was associated with glucose and lipid metabolism. For example, Epstein-Barr virus (EBV) is a gamma herpesvirus that is highly prevalent in the human population, which almost all adults are seropositive [ 36 ]. It was reported that the prevalence of EBV was significantly higher in diabetic patients than in the individuals without diabetes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that viral carcinogenesis was associated with glucose and lipid metabolism. For example, Epstein-Barr virus (EBV) is a gamma herpesvirus that is highly prevalent in the human population, which almost all adults are seropositive [ 36 ]. It was reported that the prevalence of EBV was significantly higher in diabetic patients than in the individuals without diabetes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the prevalence of EBV was significantly higher in diabetic patients than in the individuals without diabetes [ 37 ]. EBV has been indicated to manipulate host cell lipid metabolism in both epithelial and B cells, and it was indicated that manipulation of lipid metabolism may play a role in host cell transformation and carcinogenesis [ 36 ]. Therefore, the mRNA HIST1H2BM in the above pathways might play a role in participating in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…EBNA2-driven MYC expression can upregulate mitochondrial one-carbon metabolism, specifically the de novo synthesis of serine, which contributes to nucleotide synthesis, mitochondrial NADPH production and production of the antioxidant glutathione [ 88 ]. Other metabolic pathways upregulated by EBNA2-driven expression of MYC in B cells include cholesterol and lipid biosynthesis [ 89 , 90 ].…”
Section: Regulation Of Myc By Dna Tumor Virus Oncoproteinsmentioning
confidence: 99%
“…BCL2L11 expression can be induced by MYC in the absence of EBNA3A and EBNA3C in a negative feedback mechanism [93][94][95]. expression of MYC in B cells include cholesterol and lipid biosynthesis [89,90].…”
Section: Regulation Of Myc By Ebvmentioning
confidence: 99%
“…HBV induced metabolic dysregulation in heptitis has been investigated for many years, while the role of HBV in HCC metabolism remains unclear. It becomes more and more widely accepted that oncogenic DNA virus could hijack the cell metabolic machinery caused metabolic rearrangement sequentially [4].…”
Section: Introductionmentioning
confidence: 99%